The impact of non-lethal doses of pyriproxyfen on male and female Aedes albopictus reproductive fitness - Kancharlapalli, Sri Jyosthsna; Brelsfoard, Corey L. (Frontiers in Insect Science, 2024)
Introduction Control of the mosquito Aedes albopictus is confounded by its behavior due to females preferring to oviposition in small natural and artificial containers that are often difficult to remove or treat with insecticides. Autodissemination strategies utilizing highly potent insect growth regulators (IGRs) have emerged as promising tools for the control of this container-inhabiting species. The intended goal of autodissemination approaches is to use mosquitoes to self-deliver an IGR to these cryptic oviposition locations. Previous studies have focused on the efficacy of these approaches to impact natural populations, but little focus has been placed on the impacts on mosquitoes when exposed to non-lethal doses of IGRs similar to the levels they would be exposed to with autodissemination approaches. Methods In this study, the impact of non-lethal doses of pyriproxyfen (PPF) on the reproductive fitness of Ae. albopictus was investigated. Female and male Ae. albopictus mosquitoes were exposed to non-lethal doses of PPF and their fecundity and fertility were measured. To examine the impact of non-lethal doses of PPF, the expression of the ecdysone-regulated genes USP, HR3, and Vg, which are involved in vitellogenesis, was determined. Results Our results demonstrated a significant reduction in female fecundity and in the blood feeding and egg hatching rates upon exposure to non-lethal doses of PPF. Oocyte development was also delayed in PPF-treated females. Furthermore, exposure to non-lethal doses of PPF altered the expression of the genes involved in vitellogenesis, indicating disruption of hormonal regulation. Interestingly, PPF exposure also reduced the sperm production in males, suggesting a potential semi-sterilization effect. Discussion These findings suggest that non-lethal doses of PPF could enhance the efficacy of autodissemination approaches by impacting the reproductive fitness of both males and females. However, further research is needed to validate these laboratory findings in field settings and to assess their practical implications for vector control strategies.